Michael Vey : rise of the Elgen - Evans, Richard Paul (Evans, Richard Paul. Michael Vey series, 2012)
Fifteen-year-old Michael Vey, born with Tourette's syndrome and special electromagnetic powers, joins his techno-genius best friend and an alliance of other "electric" teenagers to battle powerful foes in the jungles of Peru, where Michael learns the Order of Elgen's plan to "restructure" the world.